Role of Emotional Intelligence on Retaining Faculty Members at Higher Educational Institutions: A Phenomenological Analysis of Selected Business Schools - Poudel, Mitra Bandhu (Bodhi: An Interdisciplinary Journal, 2023)
Competent faculty retention in any academic institution requires its leaders to have adequate competencies of emotional intelligence. The purpose of this study, hence, has been to examine the importance of emotional intelligence in faculty retention in higher educational institutions in Nepal. A qualitative, phenomenological approach was used to achieve the purpose of this study. In this context, eleven faculty members shared their experiences highlighting the value of emotional intelligence in their work environment. Transcription of interviews and focus group discussions were used as primary sources of data collection. Five themes and sixteen sub-themes revealed that competency factors of emotional intelligence such as empathy, self control, and inspirational leadership, conflict management, delivering services, effective communication, teamwork, and collaboration have profound roles in retaining faculty at the academic institution. According to the description of the participants, organizational policies, leadership behavior, and motivational factors also play important roles in retaining the faculty. Furthermore, it was revealed that sports, pairing protocol, spacing effect, and environmental enrichment initiatives would also enhance faculty retention from a brain science perspective. As a result, leaders who want to retain their employees for a longer period need to portray emotional intelligence at their workplace. This research, therefore, serves as a guideline for leaders at selected business schools to connect towards all ongoing debates that contribute to the body of literature as a new area of emotional intelligence in faculty retention.